The Life of Lambert Lombard (1565); and Effigies of Several Famous Painters from the Low Countries (1572) - Lampsonius, Dominicus, 1532-1599 (Book collections on Project MUSE., 2021)
"Among the earliest written texts on the history and theory of Netherlandish art, these two key writings are now available together in an English translation"--